Hand Pedal Powered Washing Machine - Abdullah, Nurmina; Mohd Amien Rais Shahadan,; Mohamad Razif Abu Bakar,; Muhammad Harris Daniel Abdullah, (Multidisciplinary Applied Research and Innovation, 2024)
The Hand Pedal Powered Washing Machine is an eco-friendly alternative to electric washing machines, operated manually through a pedal mechanism. This project specially made for students that live in hostel. By harnessing human power, it eliminates the need for electricity, making it an ideal solution for areas with limited access to power or those aiming to reduce their carbon footprint. Modern washing machines come in large sizes and draw a lot of electricity. By times, students that stay in hostel will choose to wash their clothes with their own hands. As a result, this project was started to create a small-sized washing machine that doesn't require electricity, specifically to address the issue for students living in hostel. During FYP 1, activities such as choosing and creating design concepts, three-dimensional painting, and more was happening to make sure FYP 2 going smoothly. In the end, this project demonstrates how washing and rinsing clothes can be done quick and easy in comparison to other washing machines.